Analisis Laporan Keuangan “PT Bank BTPN Syariah TBK.” - Juliawati Juliawati; Michelle Winovsky; Evelyn Juviani; Celine Patrisia Sinurat; Elita Elita; Angelin Alienta; Sari Dewi (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Initially in 2008, BTPN launched a sharia business unit as part of an effort to expand sharia banking services in Indonesia. Where then this sharia business unit developed rapidly and in 2014, on July 14 2014 to be precise, BTPN Syariah was officially established as a separate sharia bank with a license from the Financial Services Authority (OJK) and became the 12th Sharia Commercial Bank in Indonesia. Since its inception as a BTPN Sharia Business Unit, BTPN Syariah has continued to focus more on being able to reach and provide banking services to the inclusive segment, namely to inclusive communities. In line with this commitment, BTPN Syariah provides assistance, access, and banking products and services that comply with sharia principles, with the aim of helping customers achieve their dreams and improve their quality of life (BTPN Syariah Tbk Annual Report 2022, 2022).